Individuals motivated to participate in adherence, care and treatment (imPACT): development of a multi-component intervention to help HIV-infected recently incarcerated individuals link and adhere to HIV care. (December 2016) - Golin, Carol; Knight, Kevin; Carda-Auten, Jessica; Gould, Michele; Groves, Jennifer; L.White, Becky; Bradley-Bull, Steve; Amola, Kemi; Fray, Niasha; Rosen, David; Mugavaro, Michael; Pence, Brian; et al.
Abstract Background Policy-makers promote a seek, test, treat and retain (STTR) strategy to expand HIV testing, support linkage and engagement in care, and enhance the continuous use of antiretroviral therapy for those HIV-infected. This HIV prevention strategy is particularly appropriate in correctional settings where HIV screening and treatment are routinely available yet many HIV-infected individuals have difficulty sustaining sufficient linkage and engagement in care, disease management, and viral suppression after prison release. Methods/design Our research team developed Project imPACT (individuals motivated to Participate in Adherence, Care and Treatment), a multi-component approach for HIV-Infected recently incarcerated individuals that specifically targets their care linkage, retention, and medication adherence by addressing multiple barriers to care engagement after release. The ultimate goals of this intervention are to improve the health of HIV-infected individuals recently released from prison and reduce HIV transmission to their communities by maintaining viral suppression. This paper describes the intervention and technology development processes, based on best practices for intervention development and process evaluation. These processes included: 1) identifying the target population; 2) clarifying the theoretical basis for intervention design; 3) describing features of its foundational interventions; 4) conducting formative qualitative research; 5) integrating and adapting foundational interventions to create and refine intervention content based on target audience feedback. These stages along with the final intervention product are described in detail. The intervention is currently being evaluation and a two arm randomized, controlled trial in two US state prison systems. Discussion Based on a literature review, qualitative research, integration of proven interventions and behavioral theory, the final imPACT intervention focused on the transition period two to three months before and three months after prison release. It emphasized pre-release readiness, pre- and post-release supportive non-judgmental counseling, linking individuals to a HIV care clinic and technological supports through videos and text messages. This article provides a useful model for how researchers can develop, test, and refine multi-component interventions to address HIV care linkage, retention and adherence. Clinical trial registration NCT01629316, first registered 6-4-2012; last updated 6-9-2015.